Intrapelvic Femoral Head Dislocation without Associated Proximal Femur Fracture: A Case Report and Description of Closed Reduction Technique - S. Craig Morris; Priyantha L. Wickramanayake; Peter J. Wilton; Jonathan L. Allen (Case Reports in Orthopedics, 2019)
Traumatic hip dislocations are potentially devastating injuries, especially in young patients, and require emergent orthopedic treatment. Given the significant amount of energy required to cause these injuries, a high index of suspicion is necessary to identify related injuries. The associated injuries, direction of dislocation, and time between injury and reduction represent the known prognostic factors, based on limited available research. Intrapelvic hip dislocations represent an uncommon variant of the traumatic hip dislocation, with all previously reported cases involving ipsilateral proximal femur fractures. We present a case of intrapelvic femoral head dislocation without an associated proximal femur fracture, as well as the maneuvers used to treat the patient via a closed reduction.